Pengembangan media fun thinkers book berbasis literasi pada pembelajaran IPAS kelas IV SD Negeri Gunung Agung Kulon Progo - Ina Aryanti; Shanta Rezkita; Murniningsih Murniningsih (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study is to describe the characteristics of literacy-based Fun Thinkers Book media, describe the feasibility of literacy-based Fun Thinkers Book media, and describe student responses to literacy-based Fun Thinkers Book media in grade IV science learning at SD Negeri Gunung Agung. This type of research is Research and Development adapting the development method by Sugiyono. Data collection techniques use questionnaires, observations, interviews, and documentation. Data analysis using qualitative data analysis and quantitative data analysis. The results showed that the characteristics of literacy-based Fun Thinkers Book media contain material summaries, experimental activities, quizzes, and rewards and punishments that make it easier for students to understand the material, literacy-based Fun Thinkers Book media is very feasible to use based on the assessment of media experts with a score of 95%, material experts with a score of 92.5%, and class teachers with a score of 96.25%, and get a positive response from students with scores of 93% on limited tests and 92.5% on the main test.